2005
DOI: 10.1111/j.1439-0531.2004.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

The Sow Endosalpinx at Different Stages of the Oestrous Cycle and at Anoestrus: Studies on Morphological Changes and Infiltration by Cells of the Immune System

Abstract: The oviduct, together with its secretion, forms the environment in which gamete transport, sperm maturation, fertilization as well as early embryo transport and development occur. Morphological aspects, as well as immune cell distribution, have been described only to a limited extent regarding the pig oviduct. To better understand the reproductive physiology, more information is needed regarding morphology and infiltration of immune cells at different stages of the oestrous cycle.The aim of this study was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 43 publications
6
24
1
2
Order By: Relevance
“…Domuz böbreğindeki mast hücreleri üzerinde yapılan elektron mikroskopik incelemelerde, bu hücrelerde 3 tip granül bulunduğu bildirilmiştir (21). Memeli oviduktu spermatozoonun hareketlilik kazandığı, kapasitasyonun şekillendiği, embriyonun ve oosit II'nin bu bölgeden geçişinde beslenmesinin sağlandığı, erken embriyonik gelişmelerin gerçekleştiği önemli bir organdır (9). Bütün bu fonksiyonları yerine getiren oviduktun yapısında bulunan mast hücrelerinin yapı ve fonksiyonlarının daha detaylı incelenmesi gerektiği inancıyla bu çalışma gerçekleştirilmiştir.…”
Section: Introductionunclassified
“…Domuz böbreğindeki mast hücreleri üzerinde yapılan elektron mikroskopik incelemelerde, bu hücrelerde 3 tip granül bulunduğu bildirilmiştir (21). Memeli oviduktu spermatozoonun hareketlilik kazandığı, kapasitasyonun şekillendiği, embriyonun ve oosit II'nin bu bölgeden geçişinde beslenmesinin sağlandığı, erken embriyonik gelişmelerin gerçekleştiği önemli bir organdır (9). Bütün bu fonksiyonları yerine getiren oviduktun yapısında bulunan mast hücrelerinin yapı ve fonksiyonlarının daha detaylı incelenmesi gerektiği inancıyla bu çalışma gerçekleştirilmiştir.…”
Section: Introductionunclassified
“…It has been ascertained that, in pigs, the rate of protein synthesis in the epithelial cells of the ampulla is greater than that in the isthmus. It has been reported that the alterations that occur particularly during the prooestrus and oestrus phases bear great significance for the capacitation of the spermatozoon and the development of the oocyte (10).…”
Section: Introductionmentioning
confidence: 99%
“…Japanese quails have shown increased heterophil counts in their vagina and UVJ up to three hours after copulation (Higaki et al, 1995), similarly to the response seen in pigs (see above). Macrophages are distributed in the stroma and mucosal epithelium of laying hens and are increased in the vagina, magnum and infundibulum, but not in the SST (Zheng and Yoshimura, 1999), similarly to what is described in sows (Jiwakanon et al, 2005). The innate immunity in all segments of the oviduct in poultry is governed by β-defensins (avβD) with antimicrobial activity, namely avβD 1-5 and 7-12, that are overexpressed in the vagina of laying hens (Ohashi et al, 2005;AbdelMageed et al, 2008: Das et al, 2008.…”
Section: Semen Is Immunologically Foreign To the Femalementioning
confidence: 83%
“…The adaptive immune system is well represented in the female genitalia of poultry and pigs with both T cells (CD4+ and CD8+), B cells (IgA+, IgG+ and IgM+) and MHC class II positive antigen presenting cells (Withanage et al, 1997;Kaeoket et al, 2001c, Jiwakanon et al, 2005. The oviduct of the laying hen contains all sets of T lymphocytes largely in the lamina propria (Withanage et al, 1997), including CD8+ cells close to the epithelial lining, but rarely in the UVJ.…”
Section: Semen Is Immunologically Foreign To the Femalementioning
confidence: 99%
See 1 more Smart Citation